New insights into the role of tissue eosinophils in the progression of colorectal cancer: A literature review - Saraiva A (2018)
Introduction: Amongst the inflammatory cells implicated in the immune surveillance of colorectal cancer, a growing body of evidence suggests a role for eosinophils in carcinogenesis. We aimed to review the value of tumour-associated tissue eosinophilia (TATE) in the prognosis of colorectal cancer emphasizing the identification and measurement of tissue-infiltrating eosinophils and their association with the clinicopathological features of the disease. Material and Methods: We used PubMed and Web of Science search engines to retrieve studies that looked at the association between tissue eosinophils and colorectal cancer prognosis. Results: We selected 15 studies for our review. In the majority of the studies, eosinophils were identified in hematoxylin-eosin stained sections and scores were generated for analysis. Most of the studies pointed to tumour-associated tissue eosinophilia as a favourable prognostic marker in colorectal cancer and found an inverse association between eosinophil count and the metastatic potential of these neoplasms. The association between tumour-associated tissue eosinophilia and established prognostic markers of colorectal cancer was assessed in some studies, with inconsistent results. Additionally, tumour-associated tissue eosinophilia decreased with the adenoma-carcinoma progression of colorectal lesions. Discussion: Several mechanisms have been proposed regarding eosinophil chemoatraction to tumour tissues and eosinophil-cancer cell cross-talk, suggesting that eosinophils are actively involved in colorectal cancer progression. Although a scoring system is still lacking, tumour-associated tissue eosinophilia meets the criteria of a convenient histopathological prognosticator in colorectal cancer. Conclusion: Collectively, current evidence associates the presence of eosinophils in the colorectal cancer microenvironment with the modulation of tumour progression. The clinical impact of this finding deserves future research.